Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2017
DOI: 10.1115/gt2017-63056
|View full text |Cite
|
Sign up to set email alerts
|

Transient Power Operation of a Supercritical Carbon Dioxide Brayton Cycle

Abstract: The Naval Nuclear Laboratory has been operating the Integrated System Test (IST) with the objective of demonstrating the ability to operate and control a supercritical carbon dioxide (sCO2) Brayton power cycle over a wide range of conditions. The IST is a two shaft recuperated closed sCO2 Brayton cycle with a variable speed turbine-driven compressor and a constant speed turbine-driven generator designed to output 100 kWe. This paper presents a thermal-hydraulic lead control strategy for operation of the cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Since close to the critical point a slight change of pressure and temperature translates in a dramatic variation of the fluid thermo-physical properties (i.e. density, thermal conductivity or thermal capacity), very accurate sensors are needed to be able to regulate effectively the device and thus the overall system [59]. The characteristics of the first prototypes of turbines, compressors and Turbine-Alternator-Compressor (TAC) units designed by the different industrial and academic institutions worldwide are summarized in Tables 1 and 2 respectively.…”
Section: Turbomachinerymentioning
confidence: 99%
“…Since close to the critical point a slight change of pressure and temperature translates in a dramatic variation of the fluid thermo-physical properties (i.e. density, thermal conductivity or thermal capacity), very accurate sensors are needed to be able to regulate effectively the device and thus the overall system [59]. The characteristics of the first prototypes of turbines, compressors and Turbine-Alternator-Compressor (TAC) units designed by the different industrial and academic institutions worldwide are summarized in Tables 1 and 2 respectively.…”
Section: Turbomachinerymentioning
confidence: 99%
“…The thermal efficiency of ramjets mainly depends on numerical conditions at the inlet and outlet of the combustion chamber and the engine outlet. In another study, the effectiveness of scramjets based on the Brayton cycle [110] was primarily analyzed. The cyclic static temperature ratio (T 3 /T 0 ) was the parameter emphatically discussed in this study, and changes in the velocity and temperature of the inlet and outlet of the combustion chamber, the unit thrust, the overall efficiency, and the thermal efficiency of the propulsion system were calculated under different T 3 /T 0 values.…”
Section: Thermal Control Systemsmentioning
confidence: 99%
“…Linares et al [13] proposed a modification to RCBC that facilitate heat addition at a lower pressure to enable the use of conventional shell and tube heat exchangers in order to reduce the cost of the PHEX for CSP applications. Clementoni et al provided the steady-state [14], off-design [15] and transient [16] operational results of a 100kWe experimental facility at the Naval Nuclear Laboratory, USA. Clementoni et al [17] also reported the operational results of the test facility for different compressor inlet temperature (CIT).…”
Section: Introductionmentioning
confidence: 99%
“…Bennett et al [16] observed that the off-design cycle pressure ratio of sCO2 cycle reduces at higher ambient temperatures. Consequently, the turbine expansion ratio reduces which increases, the turbine exhaust temperature (TET) for a given TIT and since sCO2 cycles are recuperative Brayton cycles, this higher TET increases the recuperation.…”
Section: Introductionmentioning
confidence: 99%